Intellectual Disability and Potassium Channelopathies: A Systematic Review - Kessi, Miriam; Chen, Baiyu; Peng, Jing; Tang, Yulin; Olatoutou, Eleonore; He, Fang; Yang, Lifen; Yin, Fei (Frontiers in Genetics, 2020)
Intellectual disability (ID) manifests prior to adulthood as severe limitations to intellectual function and adaptive behavior. The role of potassium channelopathies in ID is poorly understood. Therefore, we aimed to evaluate the relationship between ID and potassium channelopathies. We hypothesized that potassium channelopathies are strongly associated with ID initiation, and that both gain- and loss-of-function mutations lead to ID. This systematic review explores the burden of potassium channelopathies, possible mechanisms, advancements using animal models, therapies, and existing gaps. The literature search encompassed both PubMed and Embase up to October 2019. A total of 75 articles describing 338 cases were included in this review. Nineteen channelopathies were identified, affecting the following genes: KCNMA1, KCNN3, KCNT1, KCNT2, KCNJ10, KCNJ6, KCNJ11, KCNA2, KCNA4, KCND3, KCNH1, KCNQ2, KCNAB1, KCNQ3, KCNQ5, KCNC1, KCNB1, KCNC3, and KCTD3. Twelve of these genes presented both gain- and loss-of-function properties, three displayed gain-of-function only, three exhibited loss-of-function only, and one had unknown function. How gain- and loss-of-function mutations can both lead to ID remains largely unknown. We identified only a few animal studies that focused on the mechanisms of ID in relation to potassium channelopathies and some of the few available therapeutic options (channel openers or blockers) appear to offer limited efficacy. In conclusion, potassium channelopathies contribute to the initiation of ID in several instances and this review provides a comprehensive overview of which molecular players are involved in some of the most prominent disease phenotypes.